Pengaruh Omnibus Law terhadap Kontrak Kerja: Studi di Kota Batam - Oky Mayrudin; Rina Shahriyani Shahrullah; Ampuan Situmeang (Legal Spirit, 2023)
Since it was ratified on October 5 2020, the Omnibus Job Creation Law has still reaped consternation among workers. Basically, the Omnibus Law on Job Creation was made with the aim of improving the welfare of employees. In fact, employees feel disadvantaged by the existence of the Omnibus Job Creation Law, especially in the work contract section. In the Omnibus Law on Job Creation, it is not possible for employees to become permanent employees when their working period ends for a certain time. However, there are also benefits for employees with this new rule, namely employees will receive severance pay/compensation when their working period ends. However, employers have a way of not incurring additional expenses by tweaking employee contracts to be short-term to avoid employees getting THR.